Managerial economics - Gupta, G. S. (Tata McGraw-Hill Education Private Limited, 2011)
This well-structured textbook walks readers through the full managerial economics toolkit—from demand forecasting and cost theory to pricing strategies, investment analysis, and macroeconomic considerations. With the inclusion of fresh chapters on project finance and macroeconomics, it aims to thoroughly prepare both students and practitioners for real-world decision-making backed by economic principles.